Checkpoint kinase 1 is essential for normal B cell development and lymphomagenesis. Issue 1 (December 2017) - Schuler, Fabian; Weiss, Johannes; Lindner, Silke; Lohmüller, Michael; Herzog, Sebastian; Spiegl, Simon; Menke, Philipp; Geley, Stephan; Labi, Verena; Villunger, Andreas
Abstract Checkpoint kinase 1 (CHK1) is critical for intrinsic cell cycle control and coordination of cell cycle progression in response to DNA damage. Despite its essential function, CHK1 has been identified as a target to kill cancer cells and studies usingChk1 haploinsufficient mice initially suggested a role as tumor suppressor. Here, we report on the key role of CHK1 in normal B-cell development, lymphomagenesis and cell survival. Chemical CHK1 inhibition induces BCL2-regulated apoptosis in primary as well as malignant B-cells and CHK1 expression levels control the timing of lymphomagenesis in mice. Moreover, total ablation ofChk1 in B-cells arrests their development at the pro-B cell stage, a block that, surprisingly, cannot be overcome by inhibition of mitochondrial apoptosis, as cell cycle arrest is initiated as an alternative fate to limit the spread of damaged DNA. Our findings define CHK1 as essential in B-cell development and potent target to treat blood cancer. Checkpoint kinase 1 (CHK1) is critical for intrinsic cell cycle control and coordination of cell cycle progression. Here the authors show that CHK1 loss or chemical inhibition impacts on normal B cell development, lymphomagenesis and cancer cell survival.